2017
DOI: 10.1080/24694452.2017.1308240
|View full text |Cite
|
Sign up to set email alerts
|

Digital Hegemonies: The Localness of Search Engine Results

Abstract: Every day, billions of Internet users rely on search engines to find information about places to make decisions about tourism, shopping, and countless other economic activities. In an opaque process, search engines assemble digital content produced in a variety of locations around the world and make it available to large cohorts of consumers. Although these representations of place are increasingly important and consequential, little is known about their characteristics and possible biases. Analysing a corpus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…While informative, the findings from these audits are limited due to their reliance on proxy-based or otherwise indirect data collection methodologies, a lack of controls for isolating personalization, or a focus on a subset of the components that appear in modern Google SERPs [5,32,36,43,45]. Furthermore, the measures that have been previously employed to quantify ranking similarity, like Jaccard index or edit distance, are limited in their ability to distinguish between ranking differences that occur towards the top of a ranked list and differences that occur towards the bottom.…”
Section: Google Search Auditsmentioning
confidence: 99%
See 2 more Smart Citations
“…While informative, the findings from these audits are limited due to their reliance on proxy-based or otherwise indirect data collection methodologies, a lack of controls for isolating personalization, or a focus on a subset of the components that appear in modern Google SERPs [5,32,36,43,45]. Furthermore, the measures that have been previously employed to quantify ranking similarity, like Jaccard index or edit distance, are limited in their ability to distinguish between ranking differences that occur towards the top of a ranked list and differences that occur towards the bottom.…”
Section: Google Search Auditsmentioning
confidence: 99%
“…More recently, researchers exploring localized versions of Google found that the extent to which a geographical region has developed publishing and scientific industries is strongly correlated with the locality of search results returned [5]. Another recent audit was conducted on the search engines of Google, Yahoo, and Bing during the 2016 US Congressional Elections [45].…”
Section: Google Search Auditsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to bear in mind that this data refers to search behaviour, and not to actual data production and consumption on Wikimapia and OpenStreetMap. Additionally, Internet access and Google search engine use vary nationally, reaching widely different percentages of the population (Ballatore et al, 2017). While acknowledging the limitations and noise contained in the data, Google Trends has been successfully used to investigate economic and cultural behaviours at a large scale (Preis et al 2012;Choi & Varian, 2012;Stephens-Davidowitz, 2013).…”
Section: Web Popularity Of Wikimapia and Openstreetmapmentioning
confidence: 99%
“…Not enough data is available for Sub-Saharan Africa and Central Asia. Interestingly, this spatial divergence retraces the digital divide between the Global North of high-income countries and the Global South, with medium-and low-income countries(Ballatore et al, 2017).Several explanations can be advanced in this context. First, Wikimapia originated from Russia, and might have been able to produce data about Russia and neighbouring countries more effectively.…”
mentioning
confidence: 98%